2021
DOI: 10.3390/agronomy11112196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Nitrogen with Bio-Organic Fertilizer on Soil Properties, Yield and Quality of Non-Heading Chinese Cabbage

Abstract: Fertilizer is extremely essential to increasing the yield of vegetables. However, excessively using fertilizers has had a negative impact on the yield and quality of vegetables as well as soil environment in recent years. Non-heading Chinese cabbage ‘yellow rose’ was applied to determine the influence of organic manure and inorganic fertilizer on the character of rhizosphere soil, the growth and quality of plants. There were five treatments: conventional fertilization (NF), a total nitrogen reduction of 20% (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(50 reference statements)
3
2
0
Order By: Relevance
“…On the contrary, the nitrate content of N2 was decreased and significantly lower than T1. Similar results were reported by Wang [65] and Qi [66]. Feng et al [67] also found that Bacillus megaterium enriched bio-organic fertilizer, significantly increased the vitamin C content, and decreased the nitrite content in Chinese flowering cabbage.…”
Section: Effects Of Nitrogen Reduction With Bio-organic Fertilizer On...supporting
confidence: 86%
“…On the contrary, the nitrate content of N2 was decreased and significantly lower than T1. Similar results were reported by Wang [65] and Qi [66]. Feng et al [67] also found that Bacillus megaterium enriched bio-organic fertilizer, significantly increased the vitamin C content, and decreased the nitrite content in Chinese flowering cabbage.…”
Section: Effects Of Nitrogen Reduction With Bio-organic Fertilizer On...supporting
confidence: 86%
“…This study shows that compared to the conventional fertilisation method (T1), reducing nitrogen and applying bio-organic fertiliser reduces soil pH (Figure 1). This is consistent with the results of the study by Li [5] on Fuji apples but not with those by Qi et al [37]. This may be due to the neutralisation of the slightly alkaline soil by humic acid in the bio-organic fertiliser.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, as the proportion of organic organic fertilizer nitrogen relative to synthetic fertilize nitrogen increases, both the total nitrogen accumulation in plants and grains gradually decreases, aligning with previous research findings [ 30 33 ]. Additionally, it has been observed that as the proportion of organic fertilizer replacing chemical fertilizer increases, there is a corresponding rise in organic matter content.…”
Section: Discussionsupporting
confidence: 90%